Regulation of ER-Golgi Transport Dynamics by GTPases in Budding Yeast - Suda, Yasuyuki; Kurokawa, Kazuo; Nakano, Akihiko (Frontiers in Cell and Developmental Biology, 2018)
A large number of proteins are synthesized de novo in the endoplasmic reticulum (ER). They are transported through the Golgi apparatus and then delivered to their proper destinations. The ER and the Golgi play a central role in protein processing and sorting and show dynamic features in their forms. Ras super family small GTPases mediate the protein transport through and between these organelles. The ER-localized GTPase, Sar1, facilitates the formation of COPII transport carriers at the ER exit sites (ERES) on the ER for the transport of cargo proteins from the ER to the Golgi. The Golgi-localized GTPase, Arf1, controls intra-Golgi, and Golgi-to-ER transport of cargo proteins by the formation of COPI carriers. Rab GTPases localized at the Golgi, which are responsible for fusion of membranes, are thought to establish the identities of compartments. Recent evidence suggests that these small GTPases regulate not only discrete sites for generation/fusion of transport carriers, but also membrane dynamics of the organelles where they locate to ensure the integrity of transport. Here we summarize the current understandings about the membrane traffic between these organelles and highlight the cutting-edge advances from super-resolution live imaging of budding yeast, Saccharomyces cerevisiae.